Argentina : Valuing Water - World Bank (World Bank, Washington, DC, 2021)
This report assesses water security in Argentina, using a conceptual framework developed by the World Bank. The effects of the pandemic reinforce the importance of safe access to water, hygiene, and sanitation, both as the first barrier against virus transmission and as an essential factor during recovery to mitigate secondary impacts on livelihoods and community well-being. The clear need to ensure that water is available in sufficient quantity and quality for human and productive uses, together with controlling the effects of the excess of water, highlights its central role in the economy, and in particular in securing the well-being of vulnerable communities. Argentina is already taking key steps to close water security gaps. It is increasing access to water and sanitation services with a focus on the most vulnerable; defining planning instruments such as national water plans; reinforcing tools such as the national information system for water and sanitation, the national water network information system (SNIH) and management and results plans (PGRs) for public service companies; expanding the regulatory framework with law 27,520 on minimum budgets for adaptation to and mitigation of climate change; and creating new entities such as the national directorate of drinking water and sanitation (DNAPyS). This study builds on these efforts and recommends steps to take toward becoming a more water-secure country by 2030.